Implementasi Kebijakan Moneter Ekonomi Indonesia Periode 2003-2009: Study Pemikiran M. Umerchapra - Sukarna; Faisal; Hadi, Sholikul; Husenudin, Abdul (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the Implementation of Indonesian Economic Monetary Policy for the 2003-2009 period, a study of M. Umerchapra's thoughts. The method used is a qualitative method with the results presented in a descriptive form, namely by collecting actual data, this research uses a type of library research. The aim of this thesis research is to provide an overview of M. Umer Chapra's thoughts on monetary policy instruments and opportunities for their implementation in Indonesia. The results of the research show that M. Umer Chapra's thoughts are about monetary policy instruments. In the economy it can become an important discourse to be considered and studied and even further implemented in Indonesia. It is not impossible to apply M. Umer Chapra's thoughts in Indonesia. Growth in terms of assets has also proven that Islamic Banks are an ideal bank model to encourage the progress of the country's economy. However, in terms of service quality, Islamic Banks must catch up with Conventional Banks which have been established earlier